Carcass characteristics of indigenous breeds of cattle in Nigeria - Buvanendran, V.; Ikhatua, U.J.; Abubakar, B.Y.; Olayiwole, M.B. (Cambridge University Press, 1983)
Bunaji and Sokoto Gudali breeds of cattle were fattened and slaughtered at live weights of 250, 300 or 350 kg. After the carcasses were jointed into commercial cuts, the joints of the left side were dissected into lean, bone and fat. Dressing percentage was significantly higher in Bunaji carcasses (52.5 %) than in Sokoto Gudali carcasses (50.3%). The lean percentage was nearly constant at 68-69 % at all slaughter weights whereas fat percentage increased from 10.3 at 250 kg to 14.5 at 350 kg. Bone percentage was inversely related to fat percentage. The relative growth coefficients of muscle and fat were 1.28 and 1.80, whereas that of bone was 0.59. Sigrlificant changes in proportion of carcass parts and tissues were observed with increased slaughter weight. The propor-tion of hind decreased and that of back and belly increased, while chuck and shank remained relatively unchanged. Lean percentage was relatively unchanged by slaughter weight in all carcass parts except the chuck where it increased. The greatest increase in fat percentage was in the belly (7.6%) followed in decreasing order by the back (5.4%), shank (4.9%), hind (3.0%) and chuck (1.8%). The breeds did not differ in any of the traits except dressing percentage.